Factors Associated With Improved Function and Maintenance of Sports Activities at 5 to 10 Years After Autologous Hamstring ACL Reconstruction in Young Men. Issue 4 (13th April 2017) - Hetsroni, Iftach; van-Stee, Mischa; Marom, Niv; Koch, Jonathan E. J.; Dolev, Eran; Maoz, Guy; Nyska, Meir; Mann, Gideon
Background: There are limited data regarding associated factors of return to sports activities at more than 5 years after anterior cruciate ligament (ACL) reconstruction. Purpose: To test interrelationships between patient characteristics, concomitant articular lesions, graft laxity, and maintenance of sports activities at 5 to 10 years after ACL reconstruction. It was hypothesized that at 5 to 10 years after the operation in young adult men, maintenance of greater activity level and better knee function would be associated with greater preinjury activity level, younger age at reconstruction, absence of concomitant articular lesions, and minimal graft laxity at follow-up. Study Design: Case series; Level of evidence, 4. Methods: One hundred six men with autologous hamstring ACL reconstruction between the ages of 18 and 35 years were reviewed at 5 to 10 years after surgery. Excluded patients had contralateral ACL tear, revision reconstruction, or another injury impairing function. Fifty-five patients were eligible and available for follow-up. Independent variables included preinjury Tegner score, time interval from injury to surgery, smoking status, age, articular lesions, KT side-to-side difference, and pivot-shift grade. Main outcome measures were Tegner activity level, International Knee Documentation Committee (IKDC) subjective score, and Knee injury and Osteoarthritis Outcome Scale (KOOS) score at 5 to 10 years after surgery. Results: Greater Tegner activity level at follow-up was associated in a regression model with greater preinjury Tegner activity level (correlation coefficient, 0.423; P = .01), lower KT difference (correlation coefficient, –0.278; P = .04), and negative pivot shift (correlation coefficient, –0.277; P = .05). Younger age at operation predicted return to greater Tegner activity level in a univariate analysis (correlation coefficient, –0.266; P = .05) but not in a regression model (not significant). Chondral lesions at surgery predicted lower IKDC subjective scores (71.4 ± 14.3 vs 84.1 ± 11.5; P < .01) and KOOS scores but did not affect maintenance of sports activities. Conclusion: At 5 to 10 years after autologous hamstring ACL reconstruction in young men, predictors of greater sports activity level are primarily high preinjury activity level and reestablishment of knee laxity. Younger age at operation and moderate chondral lesions have lower impact in this respect.